An Efficient Scheme for Industrial Internet of Things Using Certificateless Signature. (20th July 2021) - Muhammad, Ali; Amin, Noor Ul; Ullah, Insaf; Alsanad, Ahmed; Hussain, Saddam; Al-Hadhrami, Suheer; Uddin, M. Irfan; Khattak, Hizbullah; Khan, Muhammad Asghar
Abstract : Currently, hyperelliptic curve cryptography (HECC) got attractions towards low power devices such as Industrial Internet of Things (IIoT). As we all know, it has the capability of utilizing low key size, which can be suitable for IIoT environment. Inspired by the aforementioned property of HECC, we proposed an efficient scheme for IIoT using certificateless signature with the help of HECC. The presented approach is proven to be unforgeable against the challenges of type I and type II attackers. We tested the security of the designed approach through Automated Validation of Internet Security Protocols and Applications (AVISPA). We also performed the computational and communicational cost comparisons with already existed schemes, and it is observed from our analysis that our scheme is computationally efficient and needs low communication cost.